2006
DOI: 10.1385/comp:32:1:34
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes, Health Status, and Medical Resource Utilization After Bariatric Surgery

Abstract: Surgical results, economic consequences, and shortterm health of obese patients were evaluated before and after bariatric surgery. Of 35 patients in Mayo Health Plan Arizona eligible for bariatric surgery and scheduled for gastric restriction with Roux-en-Y gastrojejunostomy, 22 (7 men, 15 women) completed pre- and postoperative (6- and 12-mo) short form (SF)-12 Health Surveys. Nineteen patients had open bariatric procedures and 3 had laparoscopic procedures. Comorbid conditions, hospital course, weight loss, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 8 publications
0
15
1
1
Order By: Relevance
“…This study contradicts previous research showing cost savings after bariatric surgery in a general population (17–18) and among individuals with type 2 diabetes (10, 19) as well as research showing that bariatric surgery is cost-effective among the severely obese with diabetes (20). It is consistent with recent research showing higher health care expenditures after bariatric surgery (21) and higher hospital use after Roux-en-Y gastric bypass (22).…”
Section: Discussioncontrasting
confidence: 99%
“…This study contradicts previous research showing cost savings after bariatric surgery in a general population (17–18) and among individuals with type 2 diabetes (10, 19) as well as research showing that bariatric surgery is cost-effective among the severely obese with diabetes (20). It is consistent with recent research showing higher health care expenditures after bariatric surgery (21) and higher hospital use after Roux-en-Y gastric bypass (22).…”
Section: Discussioncontrasting
confidence: 99%
“…Fifty six percent ( n = 43) of studies' data is predominantly is sourced from or originated from the USA . Studies also originated from Sweden 10% ( n = 8), Australia 8% ( n = 6), UK 8% ( n = 6), Canada , and the remainder of the included studies each for France ( n = 2),Germany , (Austria, Italy, Spain) , Spain , Norway , Portugal , the Netherlands , Finland , South Korea , Brazil ( n = 2) and Mexico .…”
Section: Resultsmentioning
confidence: 99%
“…This relative low fulfilment of demand may be challenged in the future by the favourable long-term results and good overall economy with this type of surgery. In a 1-year follow-up of 35 bariatric Roux-en-Y patients, Gorman et al [5] demonstrated good surgical outcome, significant weight loss (i.e., 35%), improved physical and mental health status, and an annual US$1300 saving in health expenditure per operated patient. Their results [5] are confirmed by the study of Myers and coworkers [6 ], who found a 53% weight reduction and considerable improvements in quality of life.…”
Section: Treatment Of Morbid Obesitymentioning
confidence: 99%